Infections related to health care: knowledge, attitude and practice of the nursing team (Research, Society and Development, 2020)
Infections related to health care have a negative impact on the well-being of patients, and reflect on high morbidity and mortality rates, as well as increasing economic expenditures for the hospital institution, both in material resources and in professionals. The objective of this study was to analyze the knowledge of the nursing team about infections related to health care and its role in the prevention and control of this disease. The research was descriptive with a qualitative approach, related to the performance of nursing care to hospitalized patients. The research scenario covered all the patient assistance sectors of a hospital in Northwest of  São Paulo city, and the subjects evaluated were nurses, auxiliaries and nursing technicians, who voluntarily responded to a semi-structured and self-administered questionnaire. The obtained data were grouped by similarity and analyzed statistically. It was verified that the majority of nursing professionals had knowledge about the transmission, prevention and treatment of infections related to health care. However, it is of fundamental importance to highlight that, although the employees have mastery over the problematic in question, the health institutions must offer conditions so that the nursing professionals can develop their activities according to the needs of the hospitalized patient, thus avoiding the transmission and spread of disease.